2009
DOI: 10.1080/01480540902862244
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related difference in the toxicity of 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)benzotriazole in rats: Relationship to the plasma concentration,in vitrohepatic metabolism, and effects on hepatic metabolizing enzyme activity

Abstract: Previously, we showed that the toxic susceptibility of male rats to an ultraviolet absorber, 2-(2'-hydroxy- 3',5'-di-tert-butylphenyl)benzotriazole (HDBB), was nearly 25 times higher than that of females. The present study aimed to clarify the mechanism of gender-related differences in HDBB toxicity. Male and female rats were given HDBB by gavage at 0.5, 2.5, or 12.5 mg/kg/day for 28 days, and plasma HDBB levels were measured at various time points by using liquid chromatography-tandem mass spectrometry. HDBB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As for HDBB, we previously found that there was no sex-related difference in blood HDBB levels, and in the blood, no metabolites were detected. This finding suggests that the sex-related difference in HDBB toxicity is attributable exclusively to sex-related difference in toxicodynamic factors (Hirata-Koizumi et al, 2009a).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As for HDBB, we previously found that there was no sex-related difference in blood HDBB levels, and in the blood, no metabolites were detected. This finding suggests that the sex-related difference in HDBB toxicity is attributable exclusively to sex-related difference in toxicodynamic factors (Hirata-Koizumi et al, 2009a).…”
Section: Discussionmentioning
confidence: 83%
“…The sex-related difference in HDBB toxicity was reduced by castration (Hirata-Koizumi et al, 2008a) and was not observed in preweaning rats (HirataKoizumi et al, 2008b). In contrast, there was no sex-related difference in plasma HDBB levels in young rats administered HDBB (Hirata-Koizumi et al, 2009a). These findings suggest that toxicodynamic factors account for sex-related differences in HDBB toxicity (HirataKoizumi et al, 2009b).…”
Section: Introductionmentioning
confidence: 88%
“…These results indicate no gender‐related differences in the susceptibility to toxic effects of HDBB in preweaning rats. The rate of changes in the relative liver weight clearly showed a lack of gender‐related differences in HDBB hepatotoxicity in preweaning rats (Figure 4 (Hirata‐Koizumi et al. 2009).…”
Section: Gender‐related Difference In Toxicitymentioning
confidence: 99%
“… Plasma 2‐(2′‐hydroxy‐3′,5′‐di‐ tert ‐butylphenyl)benzotriazole (HDBB) concentrations against time after HDBB administration to male and female rats. HDBB was given by gavage to male and female rats for 28 days, starting at 5 weeks of age, and blood samples were collected from the jugular vein before and 1, 2, 5, 8, and 24 hours after the 28th dose (Hirata‐Koizumi et al. 2009).…”
Section: Gender‐related Difference In Toxicitymentioning
confidence: 99%
See 1 more Smart Citation